If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-2+7n)-2(n+4)=-52
We move all terms to the left:
3(-2+7n)-2(n+4)-(-52)=0
We add all the numbers together, and all the variables
3(7n-2)-2(n+4)-(-52)=0
We add all the numbers together, and all the variables
3(7n-2)-2(n+4)+52=0
We multiply parentheses
21n-2n-6-8+52=0
We add all the numbers together, and all the variables
19n+38=0
We move all terms containing n to the left, all other terms to the right
19n=-38
n=-38/19
n=-2
| (3x-2)=(4x+1) | | 8r+7=-5+6r | | -7-3k=-3k | | 127=5a-4(-10a+2) | | -3x+13=1-x+8 | | -198=9(-5x-7) | | -50+5x+10+1/6x=-9 | | 58=4v+6 | | -3+7x=2+6x | | v/3-16=-13 | | -.2x+1.4x+8=11. | | 4n-3+2n=15 | | -6(3x+109)=120 | | -50+5x+1-+1/6x=-9 | | -f+7f=6f | | 13h-7h=6 | | -1+5x=2+6x | | (15x+-21)+(x+63)=0 | | 3+-v=6 | | -1+7x=2+7x | | x(x-46)+1/2x+x(x-35)+x=360 | | 3n-52=-45n | | 4(x+1)-6x=28 | | 8x-4(x-2)=9x+23-4x | | 18x+9=7x+14 | | 6=k/4+9 | | -1+7x=2+8x | | 5x+13=11x-73 | | -1+7x=2+6x | | 3+3(a-1)-2a=53+3(a−1)−2a=5 | | y/3+-13=-17 | | -1+7x=2+4x |